IMPACT OF DIFFERENT ESTRUS SYNCHRONIATION METHODS ON REPRODUCTIVE PARAMETERS OF KARADI AND ARABI EWES IN ERBIL REGION - E. A. H. Al-Marzani; M. S. Barwary (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was carried out to compare the effects of intravaginal FGA sponges to synchronize estrus on reproductive performance of the Karadi and Arabi ewes , 30 for each breed at 2-4 years during the breeding season were used. Ewes from each breed were equally and randomly distributed into three groups. The first group was treated with vaginal sponges saturated with (40 mg) of FGA within a period of 14 days (T1). The second group administrate with the FGA and is injected with a dose of 400 IU of the PMSG hormone  (T2). The third group treated with a dose of 0.5 ml/head of PGF2α hormone (T3)  on the day of sponge removal, was injected at. The result of the study showed a non-significant increase in the estrous rate, fertility rate and Prolificacy between Different groups regardless type of breed. Different treatments showed a significant difference (p≤ 0.05) in the pregnancy length, the T3 group showed the shortest period and the highest lambing number in comparison with T1 and T2. Birth weight increased significantly (p≤ 0.05) in T1 and T3 (4.413, 4.310) kg respectively with a slight difference between the Karadi and Arabi breeds. In conclusion, exogenous hormonal treatments in a combination of FGA sponge using PMSG and PGF2α improved reproduction parameters.